2022
DOI: 10.14814/phy2.15173
|View full text |Cite
|
Sign up to set email alerts
|

Renal injury in cardiorenal syndrome type 1 is mediated by albumin

Abstract: Cardiorenal syndrome type 1 (CRS‐1) acute kidney injury (AKI) is a critical complication of acute cardiovascular disease but is poorly understood. AKI induces acute albuminuria. As chronic albuminuria is associated with worsening kidney disease and albumin has been implicated in tubular epithelial injury, we investigated whether albumin participates in CRS‐1, and whether CRS‐1 alters renal albumin handling. We report the role of albumin in in vivo and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Kidney disease progression is actually slower in albumin knockout mice than wild-type mice [ 46 ]. Albuminuria is commonly noted in severe renal disease, and in such cases albumin may promote apoptosis of the tubular epithelial cells, leading to the progressive worsening of the pathology [ 47 ]. While it is generally believed that albumin has antioxidant and antiinflammatory roles in the body, it is also true that it can propagate the detriments of oxidative stress through the effects of chemically modified albumin upon cells.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney disease progression is actually slower in albumin knockout mice than wild-type mice [ 46 ]. Albuminuria is commonly noted in severe renal disease, and in such cases albumin may promote apoptosis of the tubular epithelial cells, leading to the progressive worsening of the pathology [ 47 ]. While it is generally believed that albumin has antioxidant and antiinflammatory roles in the body, it is also true that it can propagate the detriments of oxidative stress through the effects of chemically modified albumin upon cells.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing of urinary albumin is a biomarker of early improvement in T2-CRS after CRT (Gala-Błądzińska et al, 2020). Funahashi et al (2022) suggested that improving CRS-1 outcomes might be possible through albumin resuscitation. MI-induced CRS in rats accelerates glomerular remodeling and the production of trace albuminuria (Dong et al, 2015).…”
Section: Existing Biomarkers In Crsmentioning
confidence: 99%
“…The presence of albuminuria as an essential factor in staging the severity of CKD is the result of several large population studies showing strong significant correlation between albuminuria and all-cause mortality, cardiovascular disease, and end stage renal disease (39)(40)(41). Recent in vitro studies of a type I CRS model using human kidney cells have demonstrated that albumin damages renal tubules in a dose-dependent fashion, thereby implicating it as an important pathophysiological factor further exacerbating AKI in experimental conditions (42). Albuminuria has been studied as a disease prognosis marker in both acute and chronic heart failure as well.…”
Section: Albuminuriamentioning
confidence: 99%